Main-chain biodegradable liquid crystal based on cholesteryl end-capped polycarbonate copolymers. Issue 6 (3rd May 2017) - Xu, Xiaoxu; Yang, Liqun; Chen, Guixiang; Lu, Yanhua; Hu, Jianshe; Chen, Qifan
ABSTRACT: Main-chain biodegradable liquid crystal (LC) based on cholesteryl end-capped polycarbonate copolymers was investigated. The novel LC was synthesised through ring-opening copolymerisation of trimethylene carbonate with ε-caprolactone (CL) initiated by cholesterol, without adding any catalyst. The chemical structure of the resulting polymers was confirmed by 1 H NMR. The liquid crystalline properties were validated by X-ray diffraction, differential scanning calorimetry and polarising optical microscopy. The results showed that the synthesised polycarbonate copolymers Chol-(TMCL)x + y exhibited liquid crystallinity in particular temperature ranges because of the incorporation of the cholesterol moieties. Furthermore, the effect of CL content on the mesomorphism properties of Chol-(TMCL)x+y was also investigated; the higher the CL content, the lower the mesomorphism properties. It might be attributed to the hindered orientation of LC caused by the crystallinity of the poly(ε-caprolactone) (PCL) segments in the polymer chain. Graphical Abstract: